Studies in law, politics and society. Vol. 33 - Sarat, Austin; Ewick, Patricia (Amsterdam ; Boston : Elsevier, 2004)
This volume of "Studies in Law, Politics, and Society" presents a diverse array of articles by an interdisciplinary group of scholars. Their work spans the social sciences, humanities, and law. These scholars examine law and culture, the complex intersections of law and policy, and the place of religious values in legal life. The articles published here exemplify the exciting and innovative work now being done in interdisciplinary legal scholarship.
Innovative approaches in legal theory and jurisprudence. Love and death in American jurisprudence : myth, aesthetics, law / Adam Geary -- Detour about the Viper's nest through Hegel, Adorno, and Mann's Doctor Faustus : temporal views of subject/object convergences / Joseph Jenkins. Identity in history and context. Sexual tensions of post-empire / Katherine Franke -- Dismantling the house of Plessy : a private law study of race in cultural and legal history with contemporary resonances / Imani Perry. Reading legal policies and events. A delicate task : balancing the rights of children and mothers in parental termination proceedings / Catherine J. Ross -- Revenge and spectacular execution : the Timothy McVeigh case / Jinee Lokaneeta.
Includes bibliographical references.
Description based on print version record.
Keywords: Sociological jurisprudence; Political sociology; Law & society; Law -- General